Efek Spillover Kinerja Pembangunan terhadap Kualitas Lingkungan di Sumatera, Indonesia: Peran Demokrasi dan Dampak Negatif Aktivitas Ekonomi - Sari, Raina Linda; Rahman, Arif; Nasution, Inggrita Gusti Sari; Lubis, Irsad (Jurnal Bina Praja, 2024)
Environmental issues are increasing as human activities damage ecosystems and trigger climate change. This increasing pressure has led to a concentration on development that is not only economically and socially but also environmentally oriented. In line with the spirit of the WCED in 1987, this study aims to assess the direct and spillover impacts of development performance on environmental quality in Sumatra Island. Observations from 2015 to 2022. The data used is panel data derived from the Indonesian government authorities. The research method uses a spatial autoregressive model with one nearest neighbor weighting. Previously, a cross-section dependence test was conducted to ensure the presence of spatial effects in the model. The result showed that increasing the proportion of highly educated workers will improve environmental quality in the observation province and improve the environment in the nearest neighboring province. Democracy also has strong positive direct and spillover effects. An increase in the dependency burden of workers will improve environmental quality in the observation province, with weak spillover effects. Conversely, an increase in real GRDP per capita decreases environmental quality and affects environmental quality in neighboring regions. Four determinants have a strong total effect. Meanwhile, population density and regional expenditure have no significant effect. The implication of this study is the need for intervention from the authorities to change the perspective on economic activity and regional expenditure as a whole so that economic value added does not come at the expense of the environment.